2011
DOI: 10.1103/physreva.83.052110
|View full text |Cite
|
Sign up to set email alerts
|

Quantum thermalization of two coupled two-level systems in eigenstate and bare-state representations

Abstract: We study analytically the quantum thermalization of two coupled two-level systems (TLSs), which are connected with either two independent heat baths (IHBs) or a common heat bath (CHB). We understand the quantum thermalization in eigenstate and bare-state representations when the coupling between the two TLSs is stronger and weaker than the TLS-bath couplings, respectively. In the IHB case, we find that when the two IHBs have the same temperatures, the two coupled TLSs in eigenstate representation can be therma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 56 publications
(75 reference statements)
2
48
0
Order By: Relevance
“…In these cases, if the coupling coefficients g i,k = g i,|k| only depend on the amplitude |k|, i.e., only depend on ω k equivalently, the relation (B.3) still holds, and we still have γ 11 (ω)γ 22 (ω) = |γ 12 (ω)| 2 , as used in many literatures [35].…”
Section: Appendix B Cross Spectrummentioning
confidence: 94%
“…In these cases, if the coupling coefficients g i,k = g i,|k| only depend on the amplitude |k|, i.e., only depend on ω k equivalently, the relation (B.3) still holds, and we still have γ 11 (ω)γ 22 (ω) = |γ 12 (ω)| 2 , as used in many literatures [35].…”
Section: Appendix B Cross Spectrummentioning
confidence: 94%
“…The eigen-energies and the corresponding eigen-states of the Hamiltonian for the coupled qubit system H s are obtained as follows [17]: where δ = ω 1 + ω 2 , ∆ = ω 1 − ω 2 , Ω = √ ∆ 2 + λ 2 is the Rabi frequency, and θ ∈ [0, π] is the mixing angle defined by tan θ = λ/∆. In the symmetric qubit case ∆ = ω 1 − ω 2 = 0, we have θ = π/2.…”
Section: Model and Master Equationmentioning
confidence: 99%
“…It can be shown that in the eigen-state representation, the coherence at the equilibrium steady state vanishes, i.e., ρ 34 = ρ 43 = 0, in agreement with decoherence. The populations can be found to be [17]…”
Section: Entanglement and Coherence In The Equilibrium Situationmentioning
confidence: 99%
“…The theory has a wide variety of applications, with similar formalisms being used to describe superconducting qubits [46], atomic and molecular spectroscopy [47,48], plasmonic dimers [49], and waveguides [50,51]. The utility of the theory has allowed for a range of phenomena to be investigated, including entanglement [52][53][54][55][56][57], decoherence [58], quantum processing [59], and coherent energy transfer [60,61].…”
Section: Introductionmentioning
confidence: 99%